2020
DOI: 10.1371/journal.pone.0243040
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of rapid hepatitis C antibody assays in freshly collected whole blood, plasma and serum samples: A multicentre prospective study

Abstract: Background This study evaluated performance of two hepatitis C virus (HCV) rapid diagnostic tests (RDTs) performed by intended users in resource-limited settings. Methods Testing was conducted at three facilities in two countries (Georgia, Cambodia) using matched fingerstick whole blood, plasma and serum samples. Investigational RDTs were compared with a composite reference standard (CRS) comprised of three laboratory tests, and a reference RDT. Results In matched samples from 489 HCV positive and 967 HCV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“… 7 36 The performance of the anti-HCV screening test was estimated based on a published review of multiple screening technologies, of which we used data on the performance of the SD Biosensor Standard Q HCV test on account of its superior performance. 37 The performance of POC NAT testing was estimated based on two studies that reported the performance of the GeneXpert POC system under field conditions ( table 1 ). The performance of centralised NAT testing was based on a synthesis of results of evaluations of the performance of the cobas ® 6800/8800 system under field conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 36 The performance of the anti-HCV screening test was estimated based on a published review of multiple screening technologies, of which we used data on the performance of the SD Biosensor Standard Q HCV test on account of its superior performance. 37 The performance of POC NAT testing was estimated based on two studies that reported the performance of the GeneXpert POC system under field conditions ( table 1 ). The performance of centralised NAT testing was based on a synthesis of results of evaluations of the performance of the cobas ® 6800/8800 system under field conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The population prevalence of HCV in Pakistan was obtained from the published literature 7 36. The performance of the anti-HCV screening test was estimated based on a published review of multiple screening technologies, of which we used data on the performance of the SD Biosensor Standard Q HCV test on account of its superior performance 37. The performance of POC NAT testing was estimated based on two studies that reported the performance of the GeneXpert POC system under field conditions (table 1).…”
Section: Methodsmentioning
confidence: 99%
“…12,31 The performance of the anti-HCV screening test was estimated based on a published review of multiple screening technologies, of which we used data on the performance of the SD Biosensor Standard Q HCV test on account of its superior performance. 32 The performance of POC NAT testing was estimated based on multiple studies that reported the performance of the GeneXpert POC system under field conditions. 13,33 The performance of central NAT testing was based on a synthesis of results of evaluations of the performance of the cobas ® 6800/8800 system under field conditions.…”
Section: Probabilitiesmentioning
confidence: 99%